Evaluation of an Antimicrobial Stewardship Decision Support for Pediatric Infections - McGonagle, Erin A.; Karavite, Dean J.; Grundmeier, Robert W.; Schmidt, Sarah K.; May, Larissa S.; Cohen, Daniel M.; Cruz, Andrea T.; Tu, Shin-Ping; Bajaj, Lalit; Dayan, Peter S.; Mistry, Rakesh D. (Applied Clinical Informatics, 2023)
Objectives Clinical decision support (CDS) has promise for the implementation of antimicrobial stewardship programs (ASPs) in the emergency department (ED). We sought to assess the usability of a newly developed automated CDS to improve guideline-adherent antibiotic prescribing for pediatric community-acquired pneumonia (CAP) and urinary tract infection (UTI).Methods We conducted comparative usability testing between an automated, prototype CDS-enhanced discharge order set and standard order set, for pediatric CAP and UTI antibiotic prescribing. After an extensive user-centered design process, the prototype CDS was integrated into the electronic health record, used passive activation, and embedded locally adapted prescribing guidelines. Participants were randomized to interact with three simulated ED scenarios of children with CAP or UTI, across both systems. Measures included task completion, decision-making and usability errors, clinical actions (order set use and correct antibiotic selection), as well as objective measures of system usability, utility, and workload using the National Aeronautics and Space Administration Task Load Index (NASA-TLX). The prototype CDS was iteratively refined to optimize usability and workflow.Results Usability testing in 21 ED clinical providers demonstrated that, compared to the standard order sets, providers preferred the prototype CDS, with improvements in domains such as explanations of suggested antibiotic choices (p < 0.001) and provision of additional resources on antibiotic prescription (p < 0.001). Simulated use of the CDS also led to overall improved guideline-adherent prescribing, with a 31% improvement for CAP. A trend was present toward absolute workload reduction. Using the NASA-TLX, workload scores for the current system were median 26, interquartile ranges (IQR): 11 to 41 versus median 25, and IQR: 10.5 to 39.5 for the CDS system (p = 0.117).Conclusion Our CDS-enhanced discharge order set for ED antibiotic prescribing was strongly preferred by users, improved the accuracy of antibiotic prescribing, and trended toward reduced provider workload. The CDS was optimized for impact on guideline-adherent antibiotic prescribing from the ED and end-user acceptability to support future evaluative trials of ED ASPs.
Keywords: clinical decision support; user testing; antimicrobial stewardship